THE COMPETITIVENESS OF MANUAL AND MECHANIZED CORN CULTIVATION - Juniska Muria Sariningpuri; Amzul Rifin; Rokhani Hasbullah (School of Business, IPB University (SB-IPB), 2017)
In 2015, total imports of corn in Indonesia reached 3.1 million tons due to lower corn production of Indonesia. One way to overcome this is to apply the technology mechanization in the cultivation process as practiced by the country largest corn producer in the world. The purpose of this study is to know the level of competitiveness of mechanized corn cultivation and manual. In addition, it is to determine the effect of government policy on competitiveness of both type of corn cultivation. The analytical method used is the Policy Analysis Matrix (PAM). The analysis showed that mechanized corn cultivation is competitive so that the business is feasible to be developed. It is seen from the DRC and PCR- corn agribusiness based on mechanization level values that less than one is 0.54 and 0.50. The manual corn cultivation, however, only show a competitive advantage but does not have a comparative advantage. Output policy is a policy that better influence both type mechanized and manual corn cultivation.Keywords: competitiveness, corn, Policy Analysis Matrix (PAM)